(untitled) (Global Journal of Management and Business Research, 2018)
This study investigates whether impending credit rating changes affect managers’ voluntary financial disclosure behaviors. I find that firms near a credit rating change do not opportunistically alter their financial disclosure practices to manipulate rating agencies’ perceptions about corporate credit risk. In particular, firms close to a credit rating change do not selectively release good news or withhold bad news in their earnings forecasts. Nor do the firms likely issue an optimistically biased forecast or a more precise forecast for good news than for bad news. Overall, there is no evidence suggesting that credit ratings are manipulated via management earnings forecasts.